Lessons from Peru to reduce under-5 mortality: understanding program implementation and context - Patricia J. García; Anna Larson Williams; Marco H. Carcamo; Amelia VanderZanden; Agnes Binagwaho (BMC, 2024)
Abstract Background Health policymakers aiming to reduce under-5 mortality (U5M) often lack data regarding how successful interventions in other countries were implemented. The Exemplars in U5M Study identified countries that achieved significant reductions in amenable U5M. This case study in Peru used implementation research to explore the contextual factors and strategies that contributed to the successful implementation of key evidence-based interventions (EBIs). Methods This research utilized a hybrid implementation research framework and a mixed-methods approach to understand the factors associated with EBI implementation and the successful reduction of U5M between 2000-2015. A desk review of existing literature on EBIs and U5M in Peru was completed, and in-depth interviews were performed with key Peruvian informants to understand the implementation strategies employed and the contextual factors that facilitated or were barriers to success. For the purposes of this analysis, three EBIs were selected and evaluated: antenatal care visits (ANC), facility-based deliveries, and infant vaccination. Results Between 2000-2015, the percent of mothers attending at least four antenatal care visits rose from 69% to 96.9%, and the percent of facility-based deliveries increased from 56 to 91%. Three doses of the tetanus/diphtheria/pertussis vaccine, widely acknowledged as a key global health indicator, reached 90% by 2015. Key informants noted that economic growth, financial reforms, strong national commitment to reduce poverty in Peru, and national prioritization of maternal and child health, were important contextual factors that contributed to the successful reduction of U5M. They noted key strategies that helped achieve success during the implementation of EBIs, including utilization of data for decision-making, adaptation driven by cultural sensitivity to address gaps in coverage, and a focus on equity and anti-poverty initiatives with the participation of government, civil society, and political parties to assure continuity of policies. Conclusion Several EBIs contributed to the successful reduction of U5M in Peru between 2000-2015. Strategies such as the focus on equity throughout the study period contributed to an increase in coverage of EBIs like ANC visits, facility-based deliveries and infant vaccination which worked to reduce U5M. Understanding how Peru successfully implemented programs that reduced preventable infant and child deaths could be useful to replicating this substantial public health success in other low- and middle-income countries.